PERILAKU PETUGAS KESEHATAN DALAM PENANGANAN LIMBAH MEDIS DI RUMAH SAKIT UMUM DAERAH ULIN BANJARMASIN - Maironah Maironah; Darni Subari; Mariani Mariani; Efansyah Noor (EnviroScienteae, 2011)
Hospital waste is an invaluable, unusable and expelled material, which is divided into medical and non medical waste. It is also categorized as radiology, infectious and common solid or domestic waste. (Health Department of Indonesia, 1992). As a public health service, hospital always produces medical or non-medical waste such as clinic, pathology and radioactive waste. It has been organized well according to the rules on health law. Remember that these are dangerous and causing infections, pollution of water, air and soil, accident factor and aesthetics problem. It is purposed to mark the knowledge, attitude and act of health officers on solving medical waste problem in order to know the relation between the predisposition factors (education, year of work, knowledge and attitude), motivating factors (hospital policy, employers motivation) and supporting factors (facilities, information) with the health officers’ attitude on solving medical waste problem, as advices for RSUD Ulin, Banjarmasin, in order to develop the quality on giving services. Those things are profitable to compare the medical waste problem solving with the law. Knowledge, attitude and act of the RSUD Ulin health officers are appraised well.-            There is significant relation between variable (education, knowledge, attitude and facilities providing) with an action of health officer on solving medical waste problem.-            There is no significant relation between the year of work variable, hospital policy, motivation and information with the attitude of health officers on solving medical waste problem.The RSUD Ulin organizers have to relocate and rearrange the place to throw away the medical waste according to the standard health requirements, organizing standard code, standard procedures, socializing the health officers, patient and their family, visitor and people around the hospital trough available media networks.